161 300 Patient Experience with Same Day Surgery for Artificial Urinary Sphincter Insertion - A Safe and Efficient Option. Issue 1 (1st April 2022) - Dropkin, B.; Sanders, S.; Kavoussi, M.; Shaaban, A.; Joice, G.; Hudak, S.; Lotan, Y.; Morey, A.
ABSTRACT: Introduction: Prior research has questioned the need for overnight observation (OBS) following artificial urinary sphincter (AUS) surgery. Objective: We sought to analyze our institutional experience transitioning from OBS to same day surgery (SDS) for AUS surgery. Methods: We retrospectively reviewed AUS surgeries performed by a single surgeon at our tertiary academic medical center between 08/2013 and 03/2020. Medical records were reviewed for patient demographics, immediate postoperative complications, timing of postoperative discharge, need for readmission, emergency department (ED) visit, outpatient phone call, or non-routine clinic visit within 7 days of discharge, and need for device explant or revision within 90 days of discharge. Patients were grouped based on discharge status: OBS vs. SDS. Catheters were removed prior to discharge (OBS group) or self-removed at home (SDS group) on the morning of postoperative day 1 (POD1). Cost savings associated with SDS were estimated using room and bed charges from a contemporary group of AUS patients (09/2017 through 08/2020). Student's t and Chi-squared tests were used to compare groups. Results: We identified 528 men who met inclusion criteria. Men in the SDS group (n = 308) were more likely to have undergone a virgin AUS insertion and were slightly younger and healthier (Table). Men in the OBS group (n = 220) were more likely to suffer an immediate postoperative complication and to be readmitted within 90 days of surgery. The groups did not vary with respect to multiple other perioperative outcomes measures. Among patients who underwent AUS surgery between 09/2017 and 08/2020, those with OBS status (n = 39) had mean additional room and bed charges of 745 ± 302 vs. none for SDS patients (n = 183). Conclusions: SDS for AUS insertion is safe, effective, and associated with significant cost savings. Routine overnight observation after AUS insertion appears to be unnecessary. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Boston Scientific and Coloplast